Predisposition Factors in Exclusive Breastfeeding in Infants-Literature Review - Subagyo; Suparji; Nana Usnawati (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background. Nutritional intake inthe first thousand days of a child’s life up to 2 yesars old is very important for growth and development. The low number of exclusive breasfeeding is still to be concern of the Indonesian governmnet .Based on data from Magetan District Health Office in 2019, the coverage of exclusive breastfeeding in the Poncol Puskesmas was 48,4 %. The purpose of this systematic literature review is to systematically review some of the results of recent research on the drivers that influence the success of exclusive breastfeeding, namely the factors of knowledge, education, employment, and attitude.The type of research used is systematic literature review (SLR) using the Preffered Reporting Items for Systematic Review and Meta Analysis (PRISMA) approach. The database used are DOAJ and SINTA (Garuda), the last 5 years publication limits, analytical research, cross sectional research designs, full text articles, research areas are Indonesia. From the research results found 546 journals and after screening obtained 9 relevant journals. Regarding education, 3 out of 4 journals stated that there was a relationship between education and exclusive breastfeeding. On the employment factor, 4 out 5 journals stated that there was a relationship between wprk and exclusive breastfeeding. In the knowledge factor, all of journals stated that there was a relationship between knowledge and eclusive breastfeeding. While in the attitude factor, 3 out of 4 journals stated that there was a relatioship between attitude and exclusive breastfeeding.The majority, of journal state that there is relationship between education, knowledge, employment, and attitude of mother’s breatfeeding. It is hoped that the results of this review will be able to bring change to readers, especially health workers who have a very important role in providing education and promotion regarding exclusive breastfeeding.